Fel d 1–derived peptide antigen desensitization shows a persistent treatment effect 1 year after the start of dosing: A randomized, placebo-controlled study - Patel, Deepen; Couroux, Peter; Hickey, Pascal; Salapatek, Anne Marie; Laidler, Paul; Larché, Mark; Hafner, Roderick P. (Journal of allergy and clinical immunology, 2013)
Allergic rhinoconjunctivitis is an increasingly common source of morbidity, with sensitivity to cats accounting for 10% to 15% of disease burden. Allergy to cats is also a major risk factor for the development of asthma. We sought to probe the persistence of the treatment effect of a novel Fel d 1–derived peptide antigen desensitization (Cat-PAD) 1 year after the start of treatment in subjects with cat allergy–induced rhinoconjunctivitis after standardized allergen challenge. In a randomized, double-blind, placebo-controlled, parallel-group clinical trial, subjects attended an environmental exposure chamber in which they were exposed to cat allergen before and after treatment with 2 different regimens of Cat-PAD over a 3-month period. Clinical efficacy was assessed as a change in total rhinoconjunctivitis symptom scores 18 to 22 weeks and 50 to 54 weeks after the start of treatment. Treatment with Cat-PAD showed greater efficacy with 4 administrations of a 6-nmol dose 4 weeks apart than with 8 administrations of a 3-nmol dose 2 weeks apart. The treatment effect of 6 nmol persisted 1 year after the start of treatment and was significantly different from that of 3 nmol (P = .0342) and placebo (P = .0104). The treatment effect was apparent on both nasal and ocular symptoms at 1 year. A short course of Cat-PAD improves the ocular and nasal components of rhinoconjunctivitis symptoms in subjects with cat allergy, with the treatment effect persisting 1 year after the start of treatment.